Characterization of M1A2 monoclonal antibody and in vitro cytotoxicity assessment - Bashokouh, Fatemeh (2012)
Despite all the big achievements in diagnosis and clinical advances, cancer as a life threatening illness, remains a problematic issue. Clinical successes of monoclonal antibodies confirm the capacity of immunotherapeutics to amend the demands in cancer treatment. To find a potential therapeutic and diagnostic product, several hybridoma clones were established earlier by fusion of lymphocytes from BALB/c mice sensitized with MCF7 breast carcinoma cell line and Sp20/0-Ag 14 myeloma cells. M1A2 is one of the stable hybridoma clones producing an IgM monoclonal antibody with < light chain. In this study, the M1A2 hybridoma clone was recloned by limiting dilution technique and the monoclonal antibody reactivity was screened against MCF7 and HT29 cell lines using cell-ELISA. High producer hybridoma clone was selected and the monoclonal antibody was produced in culture media (in vitro) and in ascitic fluid of peritoneal cavity of pristine primed BALB/c mice. Then the antibody was purified by an affinity chromatography on an F PLC system. The purified monoclonal antibody was characterized by immunological experiments such as immunofluorescence assay and immunohistochemistry. Then the target antigen was identified using protein techniques such as gel electrophoresis, immunoblotting and MALDI TOF/TOF mass spectrometry. Finally, the cytotoxicity potential of antibody was examined by MTT assay and complement-dependent cytotoxicity as well as antibody-dependent cellular cytotoxicity experiments. The results displayed the reactivity of M1A2 monoclonal antibody against tested human, mouse and rabbit cell lines in cell-ELISA technique. The reactivity results were further confirmed by immunofluorescence assay, which illustrated FITClabelling in cells’ cytoplasm. Immunohistochemical studies also revealed the positive staining of both human normal and cancerous tissues with M1A2 mAb with positive nuclear staining in less-differentiated carcinomas and cytoplasmic in welldifferentiated cancerous as well as normal breast, colon and ovary tissues. The flow cytometry analysis also verified the reactivity of M1A2 mAb toward both normal and cancerous cell lines. The HT29 cell line showed the highest percentage of stained cells with 90.07±1.15% followed by PBMC, HeLa and MCF7 with 88.7±0.35%, 77.3±2.66% and 52±0.76%, positive staining respectively measured by flow cytometry. Additional experiments were performed to identify M1A2 mAb target protein. A 65 kDa protein band was recognized on PVDF membrane in western blot experiment and a protein with a same molecular weight was immunoprecipitated from HT29 whole cell lysate by the M1A2 mAb. Then the m target protein was identified using MALDI TOF/TOF mass spectrometry and data mining suggested this protein belongs to heat shock protein family named Hsp60. The antibody also displays in vitro cytotoxicity toward MCF7 and PBMC with an approximate IC50 value of 403 μg/ mL. These findings support the introduction of M1A2 mAb as a new monoclonal antibody that recognize Hsp60 protein. With regard to the importance of heat shock proteins especially Hsp60 in new cancer research studies, the M1A2 mAb has the potential to develop as diagnostic and or therapeutic monoclonal antibody in future works.